DESENVOLVIMENTO, CARACTERIZAÇÃO E AVALIAÇÃO DE NANOPARTÍCULAS DE CASEÍNA CONTENDO CURCUMINA - Vieira, Daniele Gonçalves (2014)
Nanotechnology applied to nanomedicine production is considered a tool that offers advantages over its counterparts, mainly because of its small size. This technique aims to improve the physico-chemical characteristics of drugs or compounds with proven therapeutic activity, but which have a reduced pharmacokinetic profile, such as curcumin. Curcumin is a compound extracted from the rhizome of the Curcuma longa Linn plant, and has several therapeutic activities, such as antioxidant, antitumor and antifungal action. However, in its free form, it presents high chemical instability in physiological environment, reduced bioavailability and low intestinal absorption. Biodegradable polymers used to obtain nanostructured systems are interesting tools to increase the physico-chemical properties of compounds with pharmacokinetic limitations. Among them is casein, which is a natural, biocompatible polymer often used in the production of nanoparticles (Nps) because of its amphipathic structures allowing good interaction with polar and apolar compounds, as well as curcumin. Therefore, the present work proposed the development of nanoparticles of curcumin-containing casein, as well as its physico-chemical characterization and evaluation of its biological activities. The nanoparticles were obtained by the desolvation method, characterized by their average diameter, polydispersion index, Zeta potential, encapsulation efficiency, morphology, infrared spectroscopy and ray diffraction X. The storage stability and the gastrointestinal fluid release profile of the Nps were also evaluated, besides the cytotoxicity activities were determined on normal cells and on a tumor cell line and the antifungal action of Nps. The physico-chemical characterization showed that average diameter of the casein Nps containing curcumin in suspension was 167.8 ± 25.4 nm and of the lyophilized was 232.7 ± 25.7 nm. The polydispersity index presented a value of 0.33 ± 0.02 and the value of the Zeta potential found was -26.4 ± 2.5 mV, and after the lyophilization process, the value was -28, 3 ± 1.8 mV. Encapsulation efficiency presented a value of 70% ± 0.8%. The photomicrographs performed by MEV-FEG showed spherical and regular morphology of Nps. Based on the results of the infrared spectroscopy, it is possible to suggest that the method used to obtain casein Nps containing curcumin did not cause changes or changes in the functional groups characteristic of the components used to obtain Nps. In X-ray diffractograms of casein Nps containing curcumin and empty casein Nps, there were no characteristic peaks of crystallinity presented by curcumin, suggesting that there was interaction of curcumin with casein and amorphization of this nanostructured system. Regarding the stability of Nps, they remained stable when in aqueous suspension for 30 days at 8 ° C and for 15 days at 25 ° C, when they were in lyophilized form, they maintained their stability for 150 days. The release profile in the simulated gastrointestinal fluids showed that Nps presented good stability in the simulated gastric and intestinal fluid presenting a release of 4.24% (pH = 1.2), maintaining this percentage at pH = 6.8. At the end of 6 hours, the total release of curcumin was 5.39%. Nanoencapsulated curcumin showed low toxicity to normal cells compared to free curcumin when tested on a red blood cell model and in Vero cells. NPs showed antitumor activity in vitro on a tumor cell line and antifungal activity in vitro in Candida albicans. The developed nanostructured system showed physico-chemical characteristics that indicate that the nanoencapsulation process of curcumin improved its stability and increased its solubility in aqueous solutions. The nanoparticles were still presented as efficient curcumin carriers for possible biological applications.